Akad Jual Beli Makanan Dengan Tambahan Pajak Di Rumah Makan Sari Raos Cabang Kota Pekalongan Dalam Analisis Hukum Positif Dan Hukum Islam - Prisma Winda Aniva Nutqi; Karimatul Khasanah (el hisbah: Journal of Islamic Economic Law, 2022)
Sari Raos Restaurant Pekalongan City branch is one of the restaurants that applies an additional tax in the selling price of its products, but the tax burden on buyers is not notified at the beginning of the sale and purchase agreement. The purpose of this study is to find out the provisions of positive law and Islamic law on food buying and selling contracts with additional taxes and to analyze food buying and selling contracts with additional taxes at Sari Raos Restaurant Pekalongan City branch. This research includes empirical legal research that uses primary and secondary data. Based on the results of the study, the practice of buying and selling food with additional taxes at the Sari Raos Restaurant in the Pekalongan City branch if viewed from a positive law, the imposition of food taxes is a necessity that has been regulated in Law Number 28 of 2007 concerning General Provisions and Tax Procedures (KUP). ) and strengthened by Regional Regulation Number 2 of 2013 concerning Amendments to Regional Regulation of Pekalongan City Number 4 of 2011 concerning Restaurant Tax. However, if using the perspective of Islamic law, there is a tax imposition that was not notified at the beginning of the contract, it is possible to contain an element of gharar because one of the legal requirements for the object being sold is the price must be clear.